The Effects of Aromatherapy Massage on Sleep Quality of Nurses on Monthly Rotating Night Shifts. (6th July 2017) - Chang, Ying-Ying; Lin, Chao-Ling; Chang, Li-Yin
Abstract : The goal of this study is to examine the effects of aromatherapy massage on sleep quality of nurses with monthly rotating night shifts. Subjects were enrolled at a medical center in central Taiwan with overall score ≥ 5 of Pittsburgh Sleep Quality Index (PSQI) and randomly assigned to the treatment or control groups. They were validated by pretests during their first graveyard shift in the trial period and the sleep quality information was collected by using the PSQI and sleep detectors. During the second graveyard shift, the treatment group received aromatherapy massage and the control group rested in the same aromatherapy room after work. All subjects filled out the PSQI surveys and the sleep quality information was collected during massage or resting and the following night. We found that the total PSQI was significantly decreased in the treatment group following the aromatherapy massage. Specifically, the components such as subjective sleep quality, sleep disturbance, and daytime dysfunction were significantly decreased. However, there were no significant changes of average PSQI scores between the two groups before and after intervention. Taken together, our study suggested that aromatherapy massage could improve sleep quality of nurses with monthly rotating night shift.